Prevalence, associated factors and predictors of anxiety: a community survey in Selangor, Malaysia - Kader Maideen, Siti Fatimah; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj; Mukhtar, Firdaus (BioMed Central, 2015)
Background: Anxiety is the most common mental health disorders in the general population. This study aimed to determine the prevalence of anxiety, its associated factors and the predictors of anxiety among adults in the community of Selangor, Malaysia.